2014
DOI: 10.1016/j.cognition.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the limits of language: The odor lexicon of Maniq

Abstract: It is widely believed that human languages cannot encode odors. While this is true for English, and other related languages, data from some non-Western languages challenge this view. Maniq, a language spoken by a small population of nomadic hunter-gatherers in southern Thailand, is such a language. It has a lexicon of over a dozen terms dedicated to smell. We examined the semantics of these smell terms in 3 experiments (exemplar listing, similarity judgment and off-line rating). The exemplar listing task confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(143 citation statements)
references
References 63 publications
6
135
0
2
Order By: Relevance
“…Smell references appeared in a number of different conversations, in different contexts. Semai's 'olfactory dominance' is in accordance with what we know about the importance of olfaction in Aslian languages and cultures (Burenhult and Majid 2011;Majid and Burenhult 2014;Wnuk and Majid 2014). Jahai and Maniq, languages closely related to Semai, both have a preponderance of verbs dedicated to expressing specific types of odors, a semantic domain that is under-elaborated in most languages (Plank and Plank 1995).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Smell references appeared in a number of different conversations, in different contexts. Semai's 'olfactory dominance' is in accordance with what we know about the importance of olfaction in Aslian languages and cultures (Burenhult and Majid 2011;Majid and Burenhult 2014;Wnuk and Majid 2014). Jahai and Maniq, languages closely related to Semai, both have a preponderance of verbs dedicated to expressing specific types of odors, a semantic domain that is under-elaborated in most languages (Plank and Plank 1995).…”
Section: Discussionsupporting
confidence: 50%
“…As the previous discussion illustrates, the perceptual lexicon has been the subject of study from a variety of perspectives, including cross-linguistic surveys based largely on written data and questionnaires (e.g., Viberg 1983;Sweetser 1990;Vanhove 2008;Fedriani et al 2012), participant-observation in particular cultural contexts (e.g., Ritchie 1991; the articles in Majid and Levinson 2011b), and experimental studies (e.g., Dingemanse and Majid 2012;Wnuk and Majid 2014;Majid and Burenhult 2014). However, little is known cross-linguistically about the use of perception words in face-to-face conversation, a primary forum for the sharing, manipulation, and negotiation of perceptual experience through language.…”
Section: Perception Verbs and Conversational Datamentioning
confidence: 99%
See 1 more Smart Citation
“…But this view has been questioned by data from non-Western cultures (Majid, 2015). Challenging the claim that ''there is no semantic field of smells'' (Sperber, 1975, p. 116), the Aslian languages of the Malay Peninsula have well-articulated lexicons capturing smell qualities (Burenhult & Majid, 2011;Majid & Burenhult, 2014;Wnuk & Majid, 2014). For example, in Jahai, the word haR"t is used for the smell qualities shared between shrimp paste, sap of rubber tree, tiger, feces, musk gland of deer, rotten meat, and so forth; while ltp-it is used for the smell of flowers, perfumes, durian, and bearcat (Arctitis binturong).…”
mentioning
confidence: 99%
“…There are a small number of papers focused on odor detection in different ecological settings which have resulted in some interesting findingsmainly that non-industrial populations may have a better sense of smell (Sorokowska, Sorokowski, & Hummel, 2014;Sorokowska, Sorokowski, Hummel, & Huanca, 2013;Sorokowski, Sorokowska, & Witzel, 2014) . Research on olfactory language has suggested a similar relationship (Burenhult & Majid, 2011;de Valk, Wnuk, Huisman, & Majid, 2017;Majid & Burenhult, 2014;Majid & Kruspe, 2018;Majid & Levinson, 2011;Majid & Senft, 2011;San Roque, Kendrick, Norcliffe, Brown, Defina, Dingemanse, Dirksmeyer, Enfield, Floyd, Hammond, Rossi, Tufvesson, Van Putten, & Majid, 2015;Wnuk & Majid, 2014). Finally, there is a robust body of research in sensory ecology focused on anthropogenic disruptions to sensory-guided animal behavior (for example, see Boivin, Zeder, Fuller, Crowther, Larson, Erlandson, Denham, & Petraglia, 2016;Jürgens & Bischoff, 2017;Kunc, Lyons, Sigwart, McLaughlin, & Houghton, 2014;Morris-Drake, Kern, & Radford, 2016)-but much less known about the effects on humans (Hoover, 2018a(Hoover, , 2018b.…”
Section: Introductionmentioning
confidence: 99%